Gut Microbiota Profile of Infants with Breastfeeding and Mixed Feeding Patterns - Kusumaningrum, Tina; Tafroji, Wisnu; Gultom, Septiani Madonna; Putri, Nina Dwi; Hafifah, Cut Nurul; Safari, Dodi (HAYATI Journal of Biosciences, 2024)
We explore the gut microbiota profiles of 103 stool samples collected from infants at the age of 4 and 6 months in Jakarta, Indonesia. We performed 16S rRNA gene sequencing with Illumina MiSeq to identify the diversity, structure, and composition of the gut microbiota from those stool samples. Among 103 stool samples, 55 and 48 samples were collected from infants with breastfeeding and mixed feeding patterns, respectively. We found that the most abundant bacteria were Bifidobacteriales from the phylum of Actinobacteria (43.05%), Lactobacillales from the phylum of Firmicutes (28.39%), and Enterobacterales from the phylum of Proteobacteria (13.75%). The alpha and beta diversity analysis showed that the association between feeding patterns and differences in the microbial communities was not statistically significant (p-value >0.05). Our study did not show a difference in the gut microbiota pattern between the two feeding pattern groups. This result contributed to the variety of the world gut microbiota profile data in infants.